2013
DOI: 10.1097/cji.0b013e3182a80237
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of a GM-CSF-producing and CD40L-expressing Bystander Cell Line Combined With an Allogeneic Tumor Cell–based Vaccine for Refractory Lung Adenocarcinoma

Abstract: We created a vaccine in which irradiated allogeneic lung adenocarcinoma cells are combined with a bystander K562 cell line transfected with hCD40L and hGM-CSF. By recruiting and activating dendritic cells, we hypothesized that the vaccine would induce tumor regression in metastatic lung adenocarcinoma. Intradermal vaccine was given q14 days x3, followed by monthly x3. Cyclophosphamide (300 mg/m2 IV) was administered before the 1st and 4th vaccines to deplete regulatory T-cells. All-trans retinoic acid was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Clinical use of GM-K562 cells as bystander producers of GM-CSF has been reported previously in the context of vaccination of patients with advanced lung cancer(24, 25) and in patients with chronic lymphocytic leukemia (CLL)(25). In the CLL study, 22 subjects were treated with irradiated autologous tumor cells mixed with 1 × 10 7 GM-K562 cells without adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical use of GM-K562 cells as bystander producers of GM-CSF has been reported previously in the context of vaccination of patients with advanced lung cancer(24, 25) and in patients with chronic lymphocytic leukemia (CLL)(25). In the CLL study, 22 subjects were treated with irradiated autologous tumor cells mixed with 1 × 10 7 GM-K562 cells without adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Plautz, et al reported adoptive T-lymphocyte transfer in glioblastoma patients, using cells harvested from inguinal lymph nodes harvested 8 – 10 days after a single subcutaneous injection of irradiated autologous tumor cells mixed with 500 micrograms of recombinant GM-CSF(25). More recently, Ishikawa described safe treatment with autologous formalin-fixed tumor vaccine in patients with newly diagnosed glioblastoma(26).…”
Section: Discussionmentioning
confidence: 99%
“…The GM.CD40L bystander cell line [14] and the NCI-H1944 and NCI-H2122 cell lines [10] were prepared as previously described. Vaccines were produced as previously described with minor changes [10].…”
Section: Methodsmentioning
confidence: 99%
“…Vaccines were produced as previously described with minor changes [10]. Ad-CCL21 (a replication-defective adenovirus vector propagated in E1A complementing cell lines) was obtained from NCI-Frederick.…”
Section: Methodsmentioning
confidence: 99%
“…The median progression-free survival was 1.7 months and the median overall survival was 7.9 months. There was no radiologic tumor regression achieved [78]. …”
Section: Retinoids In Treatment and Chemopreventionmentioning
confidence: 99%